Off on a holiday adventure - Blyton, Enid (A wishing-chair adventure, 2019)
A magical wishing-chair short story from Enid Blyton with brand new full-colour illustrations! Imagine a magical chair that will fly you anywhere you please and grant you any wish! Lucky Peter and Mollie have just that. But on an exciting adventure, one very hot summer day, the wishing-chair loses its wings. How will everyone get home now?